Update on the Mechanisms of Tubular Cell Injury in Diabetic Kidney Disease - Chang, Jingsheng; Yan, Jiayi; Li, Xueling; Liu, Ni; Zheng, Rong; Zhong, Yifei (Frontiers in Medicine, 2021)
Increasing evidence supports a role of proximal tubular (PT) injury in the progression of diabetic kidney disease (DKD), in patients with or without proteinuria. Research on the mechanisms of the PT injury in DKD could help us to identify potential new biomarkers and drug targets for DKD. A high glucose transport state and mismatched local hypoxia in the PT of diabetes patients may be the initiating factors causing PT injury. Other mechanism such as mitochondrial dysfunction, reactive oxygen species (ROS) overproduction, ER stress and deficiency of autophagy interact with each other leading to more PT injury by forming a vicious circle. PT injury eventually leads to the development of tubulointerstitial inflammation and fibrosis in DKD. Many downstream signaling pathways have been demonstrated to mediate these diseased processes. This review focuses mostly on the novel mechanisms of proximal renal tubular injury in DKD and we believe such review could help us to better understand the pathogenesis of DKD and identify potential new therapies for this disease.